(untitled) (Dimensión Empresarial, 2025)
The objective of this research was to identify resilience indicators related to the survival of Mexican MSMEs during the health and economic contingency associated with Covid-19; as well as the profile of companies that have improved their level of competitiveness. The research is quantitative, correlational in scope and non-experimental in design. As analysis techniques, descriptive statistics, t-student hypothesis test, K-Means cluster analysis and discriminant analysis were used. It was found that 29% of the MSMEs considered in the study improved their level of sales during the pandemic; The dimension where statistically significant differences are observed is customer loyalty, corresponding to the relationship variable; and there is a resilience profile in companies that have managed to increase their competitiveness, whose characteristics are a high level of customer loyalty, a high level of relationship management with stakeholders and moderate levels of technological surveillance and management, savings and reinvestment .